The supplementation of ovine oocyte maturation medium with triiodothyronine affects the embryo development and apoptotic gene expression - ASADPOUR, R; AHMADNEJAD, F; ROSHANGAR, L; SABERIVAND, A; HAJIBEMANI, A (Journal of the Hellenic Veterinary Medical Society, 2021)
Triiodothyronine (T3) plays an essential role in different animal species’ embryonic development. The present research was designed to identify the effect of triiodothyronine on the in vitro ovine embryonic development and the expression of apoptotic genes.A total of 436 immature cumulus-oocyte complexes (COCs) were cultured for 24 h in the oocyte maturation medium supplemented with two concentrations of T3 (T-10 and T-100 ng/mL) or without T3(T-0: control group). Oocyte maturation, cleavage, and blastocyst rates were assessed under an inverted microscope as crucial indicators of embryo development.The relative mRNA abundance of BCL-2-associated X protein (BAX) and anti-apoptotic B-cell lymphoma-2 (BCL2) were determined at blastocysts (day 8 after IVF on day 0)by quantitative reverse transcription PCR.The data were analyzed by logistic regression using the GLIMMIX procedure followed by Chi-Square, and one-way ANOVA tests. The higher concentration of T3(100 ng/mL) significantly decreased cumulus expansion and blastocyst rate compared to controls (P<0.001). Additionally, a significantly higher expression level of BAX(P<0.001) and a dramatically lower expression level of BCL2 (P<0.01) were detected in the T-100ng/mL group compared to the controls.However, the relative mRNA level of BCL-2 was significantly higher in the T-10 ng/mL group compared to the control group (P<0.01).It appears that the supplementation of ovine oocyte maturation medium with T3 at high concentration (100 ng/mL) suppresses the ratio of blastocyst formation.